Design and Implementation of an IoT-Enabled Smart Plug Socket for Home Energy Management - Rokonuzzaman M.; Mishu M.K.; Islam M.R.; Hossain M.I.; Shakeri M.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric power transmission networks; Energy management; Energy utilization; Internet of things; Scheduling; Smart city; Smart power grids; Smartphones; Solar buildings; Android applications; Design and implementations; Electricity bill; Home energy management systems; Home energy managements; Internet of Things (IOT); Monitor and control; Transmit data; Energy management systems